Factors affecting non-performing assets in Indian banking system: An analysis of employee’s perception - Balyan, Sneha; singh, N P; Saraswati, (Industrija, 2025)
Abstract The presence of non-performing assets (NPAs) has a significant impact on a bank's solvency, profitability, and liquidity. This research aims to investigate the perception of bank employees regarding the occurrence of NPAs in SBI, ICICI, HDFC, and PNB. A structured questionnaire was administered to bank employees to gauge their perspectives on NPA occurrence. The study also identifies various variables influencing NPAs and provides suggestions for expediting their recovery. The paper identifies and analyzes the causes influencing non-performing assets (NPAs), and suggests appropriate strategies for monitoring and control.  The statistical tool SPSS was employed for factor analysis testing. The study compares and analyzes the factors influencing NPAs in both sectors. Some identified reasons for NPAs include Siphoning of funds for other purposes and ineffective monitoring. Lac in credit appraisal, Economic downturn Political pressure, etc.,
Keywords: Keywords: Banks, Non-Performing Assets (NPAs), Bank employees, Lack of experienced staff, Poor borrower information.